2019
DOI: 10.1111/jcmm.14400
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0136474 and MMP‐13 suppressed cell proliferation by competitive binding to miR‐127‐5p in osteoarthritis

Abstract: Osteoarthritis (OA) is a prevalent degenerative joint disease whose pathogenesis remains unclear. The research aims to investigate the roles of Circ_0136474/miR‐127‐5p/MMP‐13 axis in OA. Differentially expressed circRNAs and miRNAs in OA cartilage tissue were screened out and visualized by R project based on RNA‐seq data and microarray data respectively. qRT‐PCR was carried out for detection of relative expression levels of Circ_0136474, miR‐127‐5p, MMP‐13 and other inflammatory factors and Western blot analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…Altered expression of circRNA played an important role in the process of OA 29 31 . Zhao et al demonstrated that Circ_0136474 and MMP‐13 suppressed cell proliferation, while it enhanced cell apoptosis by competitive binding to miR-127-5p in OA 32 . Four circRNAs associated with RNF121 were selected and analyzed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Altered expression of circRNA played an important role in the process of OA 29 31 . Zhao et al demonstrated that Circ_0136474 and MMP‐13 suppressed cell proliferation, while it enhanced cell apoptosis by competitive binding to miR-127-5p in OA 32 . Four circRNAs associated with RNF121 were selected and analyzed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of circ_0136474 in OA tissue was markedly increased compared with the normal counterpart according to the microarray analysis conducted by Li et al [ 24 ]. Furthermore, cell counting kit-8 (CCK-8) assay, flow cytometry, and dual-luciferase reporter assay illustrated that overexpression of circ_0136474 in OA could inhibit the proliferation and promote the apoptosis of chondrocytes by competitive binding to miR-127-5p [ 24 ]. The immune-localization between circ_0136474 and matrix metalloproteinase 13 (MMP-13), a central regulator in cartilage degradation [ 89 ], has been confirmed by RNA fluorescence in situ hybridization (FISH) assy.…”
Section: Multifaceted Role Of Circrnas In Oamentioning
confidence: 99%
“…Recently, the relationship between OA and circRNAs has been partially elucidated. Emerging studies suggested that circRNAs could participate in the development of OA through mechanisms such as interfering chondrocytes proliferation and apoptosis [ 24 ], regulating ECM degradation [ 25 ], and inflammation [ 26 ]. Herein, in this review, we have summarized the roles of circRNAs in OA microenvironment, development, and putative treatment, as well as discussed the future directions toward circRNAs in OA.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence indicates that the dysregulation of circRNAs is closely related to the progress of various human diseases. For instance, Zhao et al found that circ_0136474 is signi cantly up-regulated in OA cartilage tissues, and this highly expressed circ_0136474 inhibits chondrocyte proliferation and promotes cell apoptosis [8]. Shen et al indicated that the overexpression of circSERPINE2 impedes the progression of OA by inhibiting human chondrocyte apoptosis [9].…”
Section: Introductionmentioning
confidence: 99%